PENGARUH MOTIVASI KERJA, PENGEMBANGAN KARIR DAN KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA DINAS PEMADAM KEBAKARAN DAN PENYELAMATAN KABUPATEN INDRAGIRI HILIR - jurnalmap map; Junaidi ÔÇÄ; Hadi Susanto (MAP (Jurnal Manajemen dan Administrasi Publik), 2021)
This study is to determine the effect of work motivation, career development and leadership that have a significant effect on employee performance at the Fire and Rescue Service of Indragiri Hilir Regency. The research uses quantitative methods with multiple linear regression data analysis techniques. The results of the study show that both partially and simultaneously have an effect on motivation, leadership and career development partially affect the performance of the employees of the Fire and Rescue Service of Indragiri Hilir Regency. Motivation as the variable that has the most dominant influence on the performance of the employees of the Fire and Rescue Service of Indragiri Hilir Regency.